Peran Media Sosial dalam Meningkatkan Literasi Kesehatan Masyarakat tentang Penggunaan Antibiotik yang Rasional di Indonesia: Cross-Sectional Study - veronica, Laila; Kusuma, Ikhwan Yuda; Wibawa, Navyzhah Aulia Aulia Putri; Khosyi, Nathania Elsa; Lauale, Evangelina Natali Theresya; Afifah, Maulina Nurul; Destiannesvi, Anggie (Universitas Harapan Bangsa, 2025)
Antimicrobial resistance is a serious global health problem, including in Indonesia, mainly due to the irrational use of antibiotics. The widespread use of social media opens up opportunities as a fast and interactive means of health education. This study aims to analyze the role of social media in increasing public knowledge about antibiotic use. The study used a cross-sectional design with an online survey conducted from December 2024 to May 2025, involving 581 respondents from various provinces in Indonesia. Data were collected through an online questionnaire covering demographics, social media usage patterns, and antibiotic knowledge. Data analysis was performed using SPSS version 27 with descriptive tests, and Chi-square. The results showed that the majority of respondents had moderate knowledge (63.5%), followed by high (34.9%) and low (1.5%). Age, gender, education, occupation, and social media usage are significantly related to knowledge levels. Older respondents, women, those with a bachelor's degree or higher, and civil servants tend to have better knowledge. Google (72.85%) and Twitter (64.29%) users also demonstrate higher knowledge levels compared to users of other platforms. In conclusion, social media plays an important role in improving public health literacy because social media has a very wide reach in Indonesia, information can be disseminated quickly and interactively, and it is easier for the public to understand educational content through social media than through conventional media such as television or brochures. Social media can be used as an effective strategy to reduce antibiotic resistance through more targeted and accessible education.